2017
DOI: 10.2166/wpt.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction survey: the case of urban water supply services in Southern Ethiopia

Abstract: Service quality and customer satisfaction are very important concepts that water enterprises must understand and measure from the customers' perspective to satisfy their needs. The main objectives of this research were to assess the level of customer satisfaction on urban water supply services of Southern Region, Ethiopia, and identify major determinants. Quantitative data were collected from 8,413 customers in seventeen towns, using a questionnaire based on the SERVQUAL model. Qualitative data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
1
8
0
6
Order By: Relevance
“…With reference to the CSI scale as defined in the methodology, the calculated CSI value of 2.54 points means that residential customers of LWC perceived public water provision in Ojota as fairly satisfactory. This overall rating of the services of LWC by its residential customers in Ojota validates existing African scholarship/literature, that public water provision in most African countries is unsatisfactory (Gowela et al, 2017;Kassa & Chernet, 2017;Zeraebruka et al, 2014) In addition to the calculated overall perception by all respondents on customer satisfaction with public water provision in Ojota, the study also determines the impact of demographic characteristics of respondents on their perceptual rating. Personal characteristics of respondents, such as sex, age, education and income status were analyzed to determine their impact on the rating of public water provision in Ojota.…”
Section: Calculated Customers' Satisfaction Rating Of Public Water Prsupporting
confidence: 80%
See 1 more Smart Citation
“…With reference to the CSI scale as defined in the methodology, the calculated CSI value of 2.54 points means that residential customers of LWC perceived public water provision in Ojota as fairly satisfactory. This overall rating of the services of LWC by its residential customers in Ojota validates existing African scholarship/literature, that public water provision in most African countries is unsatisfactory (Gowela et al, 2017;Kassa & Chernet, 2017;Zeraebruka et al, 2014) In addition to the calculated overall perception by all respondents on customer satisfaction with public water provision in Ojota, the study also determines the impact of demographic characteristics of respondents on their perceptual rating. Personal characteristics of respondents, such as sex, age, education and income status were analyzed to determine their impact on the rating of public water provision in Ojota.…”
Section: Calculated Customers' Satisfaction Rating Of Public Water Prsupporting
confidence: 80%
“…Over the years there has been an increase in the literature on different aspect of water provision, to avail policy makers with reliable information to take informed dicisions, which would lead to sustainable water provision by thier respective public water utilities. Some of these studies focused on access to improve sources of water supply, cost of water and quality and quantity issues (Ohwo & Abotutu, 2014; Ohwo, 2014a; Wagah, Onyango & Kibwage, 2010; Abaje, Ati & Ishaya, 2009) with few focusing on the service quality of the respective public water providers, using customer perception of selected variables to determine customers satisfaction/dissatisfaction (Kassa & Chernet, 2017;Gowela et al, 2017;Abubarka, 2016, Ojo, 2011. Some of the studies in the literature undertaken outside the study area have reported contrary results.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, levels of user satisfaction influence the O&M of water infrastructure. The relationship between service quality and user satisfaction has been further confirmed by recent studies in developing countries (Ellawala and Priyankara 2016;Kassa et al 2017;Nguyen et al 2018;Rustinsyah 2019). Accordingly, the government's ability to effectively address collective action problems is a critical test of its ability to fulfil the demands of its citizens to their satisfaction (Halla et al 2013).…”
Section: Discussion Of the Resultsmentioning
confidence: 80%
“…Surveys represent a basic source of information for water companies, and these can be carried out using the various methods, techniques and research tools described in publications, e.g., [22][23][24]. Increasingly, utilities engage in this type of research because, thanks to surveys, real insight into water-supply systems can be gained, with the input then utilised to improve quality of service [25].…”
Section: Introductionmentioning
confidence: 99%